Sens et usages contemporains de la laïcité - Michel Fabre
In France, there is no consensus between traditional political parties, on the left wing as well as the right about secularism. It takes different kinds of words: "open", "positive", "intransigent", "intelligent", etc. The aim of this paper is to describe the uses of this polysemic notion and to understand the origin of the conflicts between secularists. The rise of Islam, and above all, of Islamism, increase these tensions by the reintroduction of issues that the law of 1905 had regulated on the legal plane, but which remain on the ideological level: such as separation of politics from religion, sovereignty, identity and spiritual meaning. Thus tensions between liberty, secularism and worship's equality are becoming very hard.